Synthesis of [{AgO2CCH2OMe(PPh3)}n] and theoretical study of its use in focused electron beam induced deposition - Tamuliene, Jelena; Noll, Julian; Frenzel, Peter; Rüffer, Tobias; Jakob, Alexander; Walfort, Bernhard; Lang, Heinrich (Beilstein Journal of Nanotechnology, 2017)
The synthesis, chemical and physical properties of [AgO2CCH2OMen] (1) and [{AgO2CCH2OMe(PPh3)}n] (2) are reported. Consecutive reaction of AgNO3 with HO2CCH2OMe gave 1, which upon treatment with PPh3 produced 2. Coordination compound 2 forms a 1D coordination polymer in the solid state as evidenced by single crystal X-ray structure analysis. The coordination geometry at Ag+ is of the [3 + 1] type, whereby the carboxylate anions act as bridging ligands. The formation of PPh3–Ag(I) coordinative bonds results in distorted T-shaped AgPO2 units, which are stabilized further by an additional O–Ag dative bond. TG and TG–MS measurements show that 1 and 2 decompose at 190–250 °C (1) and 260–300 °C (2) via decarboxylation, involving Ag–P (2), C–C and C–O bond cleavages to give elemental silver as confirmed by PXRD studies. In order to verify if polymeric 2 is suitable as a FEBID precursor for silver deposition, its vapor pressure was determined (p170 °C = 5.318 mbar, ∆Hvap = 126.1 kJ mol−1), evincing little volatility. Also EI and ESI mass spectrometric studies were carried out. The dissociation of the silver(I) compound 2 under typical electron-driven FEBID conditions was studied by DFT (B3LYP) calculations on monomeric [AgO2CCH2OMe(PPh3)]. At an energy of the secondary electrons up to 0.8 eV elimination of PPh3 occurs, giving Ag+ and O2CCH2OMe−. Likewise, by release of PPh3 from [AgO2CCH2OMe(PPh3)] the fragment [AgO2CCH2OMe]− is formed from which Ag+ and O2CCH2OMe− is generated, further following the first fragmentation route. However, at 1.3 eV the initial step is decarboxylation giving [AgCH2OMe(PPh3)], followed by Ag–P and Ag–C bond cleavages.
Keywords: DFT; DSC; FEBID; silver(I) carboxylate; solid-state structure; TGA